ANALISIS FAKTOR-FAKTOR PEMBANGUNAN DESA DAN STRATEGI MENUJU DESA MANDIRI (Studi Kasus di Desa Batang Sangir Kecamatan Kayu Aro Kabupaten Kerinci): NANIK MANDASARI - NANIK MANDASARI, S.IP., M.Si (JURNAL ADMINISTRASI NUSANTARA, 2021)
Analysis of Village Development Factors and Strategies Towards Independent Villages (Case Study in Batang Sangir Village, Kayu Aro District, Kerinci Regency). This study aims to determine the Factors of Development of Batang Sangir Village and Strategies Towards Independent Villages. This type of research is descriptive with a qualitative approach. The research location is in Batang Sangir Village, Kayu Aro District, Kerinci Regency with a purposive sampling technique. This study uses data collection techniques: interviews, observation, and documentation. The results of this study are, the development factors in Batang Sangir Village include: (1) Natural Resources. (2) Human Resources. (3) Economy. (4) Public Services. (5) Community Participation. Batang Sangir Village applies a strategy towards independent villages from within, namely: optimizing the initiative or desire of the community to progress, optimizing the capacity / ability of the community, optimizing the capacity of the village head in organizing. Facilitate bureaucracy and facilitate constructive activities. Strengthening village officials' human resources through training and coaching and involving the community in development. Conduct village meetings which include community leaders, religious leaders. Determine productive businesses in Batang Sangir Village.